As conseqüências do assédio moral no ambiente de trabalho - Ávila, Rosemari Pedrotti de (My University, 2014)
Moral harassment is a problem that exists since the foundation of human relation. It has become in recent years a strong social concern because it is a violence that causes extremely negative impacts on the health and welfare of the victim because of the damage it causes. However, especially in the work relations, it is considered a new phenomenon from the point of view of its visibility. The discussion about the subject on the work environment is in full development, as it can be evidenced by publications of doctors, psychologists, administrators, unions, labor lawyers, worldwide. This demonstrates the concern of professionals of several areas, for the effective protection of interests of the people involved in that relationship. However, the legal and social visibility of the phenomenon has not yet taken the proportions necessary for its effective prevention and punishment. The whole time, countless victims are excluded from work, either because they are forced to resign or leave is medical license, either because they are induced to commit mistakes that justify a just cause demission. For this reason, the objective of this work is to contribute to amplify the legal and social visibility called work moral harassment. Thus, the work is proposed to clarify the moral harassment at work, through the study of the phenomenon in its origins, profile of those involved, methods, and their specificities in the work environment, as characterizing elements, focusing the violation of dignity of the human been and on the purpose of exclusion of the victims of the workplace which shows arbitrary and perverse discrimination. And to study in which ways the phenomenon receives the shelter of the Brazilian legal system, especially in light of the fundamental constitutional precepts that protect the people, and to understand the magnitude of the consequences that can generate to the victims health, to the aggressors, the environment of work, for the employer, for the organization of the company in order to devise policies for the prevention and solution to the problem. The research involves an interdisciplinary study, with analytical instruments from Medicine, Psychology, Administration and Law, through the technique of literature review, analysis of texts, journals, literature and the Brazilian legal position, as well as study of legal state, description of facts, stated or propositions, including the reconstruction of arguments of the analyzed authors, properly cited, critical position and exposure of arguments, ideas and solution to the problems raised. Remain that the information is the best weapon to prevent and combat this social problem.
A pesquisa objetiva contribuir para ampliar a visibilidade jurídica e social do fenômeno denominado assédio moral no trabalho. O assédio moral é um mal que existe desde os primórdios das relações humanas. Tornou-se nos últimos anos forte preocupação social em razão de ser uma violência que causa impactos extremamente negativos à saúde e ao bemestar da vítima, devido aos desgastes que provoca. No entanto, sobretudo nas relações de trabalho, é considerado um fenômeno novo, sob o ponto de vista de sua visibilidade. A discussão acerca do tema no universo do trabalho está em pleno desenvolvimento, como demonstram as publicações de médicos, psicólogos, administradores, sindicatos, profissionais juslaboralistas, em nível mundial. Isso demonstra a preocupação de profissionais de diversas áreas do conhecimento, para com a efetiva tutela dos interesses das pessoas envolvidas nessa relação. Entretanto, a visibilidade jurídica e social do fenômeno ainda não tomou as proporções necessárias a sua efetiva prevenção e punição. A todo instante, incalculáveis vítimas são excluídas do trabalho, seja por serem forçadas a pedir demissão ou afastarem-se para licença médica, seja por serem induzidas a cometer erros que justifiquem uma justa causa. Por essa razão, o objetivo deste trabalho é de contribuir para ampliar a visibilidade jurídica e social do fenômeno denominado assédio moral no trabalho. Nesse sentido, a pesquisase propõe a elucidar o assédio moral no trabalho, por meio do estudo do fenômeno em suas origens, perfil dos envolvidos, métodos, e suas especificidades no mundo do trabalho, como os elementos caracterizadores, com destaque para a violação da dignidade da pessoa humana e a finalidade de exclusão da vítima do ambiente de trabalho o que evidencia discriminação arbitrária e perversa. Também estudar sob que formas o fenômeno recebe a tutela do sistema jurídico brasileiro, em especial à luz dos preceitos constitucionais fundamentais que tutelam a pessoa humana, bem como conhecer a magnitude das conseqüências que pode gerar na saúde da vítima, para os agressores, para o ambiente de trabalho, para o contrato de trabalho, para a organização da empresa, a fim de traçar políticas de prevenção e solução para o problema. A pesquisa envolve um estudo interdisciplinar, com instrumentais analíticos provenientes da Medicina, Psicologia, Administração e do Direito, por meio da técnica de pesquisa bibliográfica, análise de textos de periódicos, bibliografia e da posição jurisprudencial brasileira, bem como estudo das normas jurídicas estatais, descrição de fatos, enunciados ou proposições, incluindo a reconstrução de argumentos de autores analisados, devidamente citados, posicionamento crítico e exposição de argumentos, idéias e solução para os problemas levantados. Restará demonstrado que a informação é a melhor arma para prevenção e combate dessa chaga social.
Keywords: Direito do trabalho; Assédio moral; Relações de emprego; Ambiente de trabalho; Dignidade humana; Indenização; Dano moral; Direito do trabalho; Harassment morals; Relationship of work; Environment of work; Human dignity; Indemnity